ISOLASI DNA TANAMAN PADI (Oryza sativa L.) ASAL KECAMATAN BANTAN, BENGKALIS – RIAU. - Dita Deanesia; Dewi Indriyani Roslim; Herman ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Excess of Fe in costal land in Riau Province is potential to poison the roots of plants. However,the plants have their own mechanism to overcome the Fe overload. This study was aimed to isolate the total DNAof rice plants among three local rice genotypes from Riau which are commonly planted in costal land in Bengkalis, Riau, with Fe overload resistant swamp rice variety (Mahsuri) and Fe overload sensitive rice variety (IR64). The experiment was conducted in the Laboratory of Genetics, FMIPA UR,from January to May 2014. Research methods consisted of isolation of DNA and electrophoresis. In this study isolation of DNA from five rice varieties was succesfully done. Among those DNA, concentration of total DNA which were obtained from IR64 and Amat Candu were very high.